PENGARUH JADWAL TRANSFUSI DARAH RUTIN TERHADAP PRESTASI BELAJAR ANAK THALASEMIA DI UNIT THALASEMIA RUMAH SAKIT UMUM KABUPATEN TANGERANG - Ria Setia Sari; Ismatul Hasanah (Jurnal Kesehatan, 2019)
Children with thalassemia often leave school to undergo transfusion and suffered various physical due to anemia, causing impaired school performance. The aim of this study to knowing influence of undergoing transfusion pf learning achievement in children thalassemia in thalassemia unit at general hospital Kabupaten Tangerang 2017. This study is an descriptive correlation with cross sectional design using independent t-test. The samples were 178 children with thalassemia aged 5-18 years who underwent routine transfusion at general hospital Kabupaten Tangerang. School performance in children with thalassemia was measured using academic achievement questionnaire. The results shown that have the influence between undergoing transfusion of learning achievement children thalassemia in thalassemia unit at general hospital Kabupaten Tangerang 2017. Nurses have support families to maximize routine transfusion schedules after school.